PENGARUH METODE SQ3R (Survey, Question, Read, Recite, Review) TERHADAP KEMAMPUAN MEMBACA PEMAHAMAN PADA SISWA KELAS V SD DI GUGUS 1 KOTA SAWAHLUNTO - Valentio Elnino Ramon; Yesni Yenti; Elfia Sukma; Ari Suriani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the low reading comprehension of students. This is caused by the lack of students' reading understanding. One effort that can be made to address this problem is by applying the SQ3R method. This study aims to determine the effect of using the SQ3R learning method on reading comprehension skills of fifth-grade elementary school students in Cluster I of Sawahlunto City. The type of research is quantitative research with a quasi-experimental design using a Non-Equivalent Control Group Design. The research population is fifth-grade students of Cluster I Elementary Schools in Sawahlunto City for the 2025/2026 academic year. The research sample consisted of two classes, namely grade IV of SDN 03 Aur Tajungkang as the experimental class and grade V of SDN 05 Kubang Sirakuk as the control class, with a total sample of 38 students. Data collection techniques were conducted through reading comprehension tests in the form of pretests and posttests. The data were analyzed using normality tests. homogeneity test, then continued with hypothesis testing using the Mann – Whitney U Test, and n-gain test. The results of this study obtained data with the average learning outcomes of students in the experimental class of 23.33, whereas in the control class it was 15.25. The results of the hypothesis test showed a significance value (2-tailed Sig.) < 0.001, which means < 0.05, so H₀ is rejected and H₁ is accepted. Thus, these data results can serve as evidence that the SQ3R method can be used as an effective alternative method to improve reading comprehension. After conducting the research, the researcher suggests that in the learning process, the SQ3R learning method can be applied in school learning processes as an interactive learning tool, in order to create a more effective and enjoyable learning atmosphere, which in turn impacts better learning outcomes.